Curriculum Research: Use of Color in Instructional Materials. - Frazier, Alexander; English, Marvin D. (Educational Leadership, 1959)
The article presents the background information of a study carried out to assess the influence of color on pupil achievement. The researchers null-hypothesized that there is no significant difference in the acquisition of learning when children are influenced by colored as opposed to black and white instructional materials. The role of the null-hypothesis is a very simple one. The learning achievements of the students using colored materials are pitted against the learning achievements of the students using black and white materials. If no difference in scores is revealed, then the two media are equally effective. If, however, a difference does exist, then one or the other medium must be more favorable. The research design employed was an extended Latin square. This means that one group used the colored materials while the other used the black and white materials and they exchanged media on each successive unit. Because of the controversial nature of the statistical results of this research study, the researchers decided to that supplementary double-checking would be wise in order to prepare for criticisms that may arise. Therefore, they are carrying out a careful scrutiny of all the procedures, experimental and statistical, before the results are made public.